Cyclic topology effects on the morphology of biocompatible and environment-friendly poly(ε-caprolactone) under nanoscale film confinement. Issue 28 (26th June 2020) - Xiang, Li; Ryu, Wonyeong; Kim, Jehan; Ree, Moonhor
Abstract : Quantitative grazing incidence X-ray scattering analysis combined with X-ray reflectivity using synchrotron radiation sources was explored for the first time cyclic topology effects on the nanoscale film morphology of poly(ε-caprolactone). Abstract : A series of cyclic poly(ε-caprolactone)s ( c -PCLs) with extremely high purity have been prepared and quantitatively investigated in terms of the impact of molecular topology on the nanoscale film morphological structure. Quantitative synchrotron grazing incidence small angle X-ray scattering analysis found that c -PCLs, in comparison with their linear counterparts ( l -PCLs), exclusively form a horizontal lamellar structure with a shorter long period, characterized by a thicker crystalline layer, thicker and denser interfacial layers and a thinner amorphous layer. Grazing incidence wide angle scattering analysis additionally confirmed higher crystallinities for c -PCLs, which were further supported by synchrotron X-ray reflectivity analysis. Overall, the quantitative structural analyses of this study provide for the first time comprehensive insights into cyclic topology effects on the nanoscale film morphology of biocompatible and environment-friendly PCL.